Evaluation of biokinetics and dosimetry in [131I]-NaI therapies: whole-body images quantification versus lower limb region - Bianca Lemos Lima; Jamille da Silveira Almeida; Maria da Penha Albuquerque Potiens; Rogério Alexandre Pelissoni; Marcelo Tatit Sapienza; Carlos Alberto Buchpiguel; José Willegaignon (Brazilian Journal of Radiation Sciences)
Introduction: Radioiodine therapy with iodine-131 (131I) is the most commonly performed radionuclide therapy in Nuclear Medicine[1]. When used in the treatment of differentiated thyroid cancer (DTC), it consists in the administration of a quantity of radioactive iodine to the patient in order to reduce the risk of relapse and mortality of the disease. In the presence of metastases, a higher activity of 131I may be required, thus recommending a previous dosimetric evaluation, in order to define the maximum activity to be administered to the patient. This activity should be sufficient for a higher exposure of neoplastic tissues and, at the same time, reducing exposure to healthy or critical internal organs in the dosimetry aspect[2]. Although, internal dosimetry is a method capable of giving information about the dose of radiation to be absorbed by internal organs, making possible an individualized and safe protocol for the treatment of each patient, this dosimetry is not routinely used in the nuclear medicine clinics and the patients indicated to the radioiodine therapy are treated with fixed or semifixed activities of 131I, independently of the individual biokinetic characteristics presented by them[3]. The exception to this scenario is usually in cases of patients with metastatic disease, when it is necessary to evaluate the dose to be received by the internal organs. In this context, the bone marrow is one of the most important organs for the dosimetric calculation, since it is highly radiosensitive and should receive a maximum of 2 to 3 Gy[4,5]. As the current dosimetric protocol can be performed by delimiting a region of interest (ROI) in whole body images to evaluate the biokinetics and absorbed dose by the patient, the objective of this study was to analyze the possibility that this measurement was restricted to only one thigh region. That way, it would be possible to optimize the time of adjustment of the ROIs and the processing of information for the calculations of internal dosimetry.